mTOR- and HIF-1¿-mediated aerobic glycolysis as metabolic basis for trained immunity. - O'NEILL, LUKE (My University, 2014)
Epigenetic reprogramming of myeloid cells, also known as trained immunity, confers nonspecific protection from secondary infections. Using histone modification profiles of human monocytes trained with the Candida albicans cell wall constituent β-glucan, together with a genome-wide transcriptome, we identified the induced expression of genes involved in glucose metabolism. Trained monocytes display high glucose consumption, high lactate production, and a high ratio of nicotinamide adenine dinucleotide (NAD(+)) to its reduced form (NADH), reflecting a shift in metabolism with an increase in glycolysis dependent on the activation of mammalian target of rapamycin (mTOR) through a dectin-1-Akt-HIF-1α (hypoxia-inducible factor-1α) pathway. Inhibition of Akt, mTOR, or HIF-1α blocked monocyte induction of trained immunity, whereas the adenosine monophosphate-activated protein kinase activator metformin inhibited the innate immune response to fungal infection. Mice with a myeloid cell-specific defect in HIF-1α were unable to mount trained immunity against bacterial sepsis. Our results indicate that induction of aerobic glycolysis through an Akt-mTOR-HIF-1α pathway represents the metabolic basis of trained immunity.
PUBLISHED
Keywords: myeloid cells